Implementasi Program Kerja Pengawas Dalam Peningkatan Kinerja Guru Pendidikan Agama Islam - Rohma, Ayu Alfiyatur (J-MPI (Jurnal Manajemen Pendidikan Islam), 2018)
Learning of Islamic religious education in Junior High School is very important because as learning to improve, obedient to God. Therefore, the level of teacher performance in Islamic religious education should be improved. One of the ways to improve the performance of teachers is with supervision or supervisory activities. Using the approach, training, and guidance done by PAIS supervisors so the improvement of PAI teacher performance will increase. The purpose of this study is to: (1) describe the work program of supervisors in improving the performance of Islamic religious education teachers in junior high school in Kepanjen subdistrict at the Office of the Ministry of Religious Affairs of Malang Regency (2) describe the implementation of supervisory work program in improving teacher performance PAI SMP scope in Kepanjen subdistrict at Office of the Ministry of Religious Affairs of Malang Regency (3) describe causes and solutions faced by supervisors in the implementation of supervisory work programs in improving the performance of teachers PAI scope of Junior High School in Kepanjen subdistrict at the Office of the Ministry of Religious Affairs of Malang Regency. To achieve the above objectives is using a qualitative research approach with the type of case study research. The key instrument is PAIS Supervisor at the Office of the Ministry of Religious Affairs of Malang Regency, and data collection techniques that used are observation, interview, and documentation. Data was analyzed by reducing irrelevant data, exposing data and drawing the conclusion. The result of the research indicates that (1) One of program worked of supervisor is the semester of program and program refers to basic assignment and the function of teacher that make the basic of result identification in the supervision was done and planed with group supervision together (2) Implementing of work programs supervisors in Kepanjen subdistrict namely individuals and groups (3) Implementing of supervisory work program in Kecamatan Kepanjen has various problems both the problem individually and in the groups, but with the regulation of supervisors can faced the problem with various solutions.